2010
DOI: 10.1186/bcr2466
|View full text |Cite
|
Sign up to set email alerts
|

Frequent aberrant DNA methylation of ABCB1, FOXC1, PPP2R2B and PTEN in ductal carcinoma in situ and early invasive breast cancer

Abstract: IntroductionDuctal carcinoma in situ (DCIS) is a non-invasive lesion of the breast that is frequently detected by mammography and subsequently removed by surgery. However, it is estimated that about half of the detected lesions would never have progressed into invasive cancer. Identifying DCIS and invasive cancer specific epigenetic lesions and understanding how these epigenetic changes are involved in triggering tumour progression is important for a better understanding of which lesions are at risk of becomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
4
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 46 publications
11
132
4
6
Order By: Relevance
“…Our findings fall in the middle of the reported range (33.3%) in accordance with several previous studies (19,27,(31)(32)(33). As far as the two major histological subtypes are concerned, a similar frequency of methylation was detected as previously reported (6,29,34). Interestingly, a statistically-significant relationship between RASSF1A promoter methylation and advanced T-category was found in accordance to Karray-Chouayekh et al (35) suggesting its involvement as a late event in breast tumourigenesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings fall in the middle of the reported range (33.3%) in accordance with several previous studies (19,27,(31)(32)(33). As far as the two major histological subtypes are concerned, a similar frequency of methylation was detected as previously reported (6,29,34). Interestingly, a statistically-significant relationship between RASSF1A promoter methylation and advanced T-category was found in accordance to Karray-Chouayekh et al (35) suggesting its involvement as a late event in breast tumourigenesis.…”
Section: Discussionsupporting
confidence: 82%
“…As far as invasive ductal breast carcinomas are concerned, methylation up to 32% of the cases has been reported (28,34,36) in accordance with our findings. Finally, in invasive lobular breast carcinomas, for which there are currently no data, we detected methylation in a subset of the examined cases (11.1%).…”
Section: Discussionsupporting
confidence: 81%
“…26 Muggerud et al also reported that FOXC1 knockdown suppressed cell proliferation, migration and invasion in breast cancer cells. 27 Taube et al reported that FOXC1 involvement in an epithelial to mesenchymal transition signature that correlates strongly with poor outcomes in breast cancer. 28 These reports are consistent with our results that FOXC1 may play a role in endometrial cancer migration and invasion.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…These findings suggest that most of the dramatic epigenetic changes take place during the transition from normal epithelium to DCIS and that aberrant methylation may not contribute to the development of invasion but rather play an important role in early breast carcinogenesis [58][59][60]. Recent studies, some of which have used a genome-wide methylation screen approach have described a small set of genes such as APC, CACNA1A, CDH1, FOXC1, HOXA10, MGMT, SFPR1, TFAP2A, and TWIST1 that exhibit differences in either frequency or density of methylation between DCIS and invasive carcinoma [61][62][63][64][65][66][67][68][69][70].…”
mentioning
confidence: 95%